Caractérisation interrégionale des paysages de la Belgique - Veerle Van Eetvelde; Marc Antrop (EchoGéo)
The landscapes in Belgium are exceptional diverse due to the important variation of the physical and natural conditions as well as to the long multicultural and tormented history. Belgium became gradually a federal state which made it difficult to get overall views on matters that became by regional governance such as spatial planning and heritage and landscape management. Since 1980 policies are diverging between the different regions and different concepts and approaches are used for landscape management and planning. This becomes obvious looking at the implementation of the European Landscape Convention in the three regions, in particular with the identification of landscapes. Although data sources covering the whole of Belgium have become rare, an interregional synthesis and landscape characterization for the whole of the country is presented.